Soybean Oil Epoxidation with Hydrogen Peroxide using an Amorphous Ti/SiO2 Catalyst - Campanella, Alejandrina (2004)
We report a study of the epoxidation of soybean oil and soybean methyl esters with hydrogen peroxide in dilute solution (6 wt%) using an amorphous heterogeneous Ti/SiO2 catalyst in the presence of tert-butyl alcohol. The influence of some relevant process variables such as temperature and the hydrogen peroxide-to-double bond molar ratio on performance is examined. The highest yields of epoxidized olefins were obtained upon using a H2O2 : substrate molar ratio of 1.1 : 1. Higher ratios than this were not effective for speeding up the reaction. Under the experimental conditions employed in this work, no degradation of the oxirane ring was observed.